Comparison of isothermal and nonisothermal combustion methods when evaluating semicoke for pulverized coal injection of blast furnace. Issue 1 (12th October 2022) - He, Jiangyong; Zou, Chong; Zhao, Junxue; Yu, Nan; Wang, Yi; Shi, Ruimeng
Abstract: Using semicoke instead of anthracite for pulverized coal injection (PCI) in a blast furnace can greatly reduce the cost of iron making, but the combustion performance of semicoke first needs to be accurately predicted. In this study, the combustion performances of different fuels were compared and analyzed in a drop tube furnace (DTF) and under isothermal and nonisothermal conditions. The results showed that semicoke had a better combustion performance than coal in the DTF. Isothermal combustion provided a more consistent performance evaluation of the fuels because the effect of volatiles was eliminated. Nonisothermal combustion significantly differed from the DTF results because of the influence of volatiles; after the fuels received high‐temperature treatment for devolatilization, the combustion performance was consistent with the DTF results. The influencing factors for the fuel combustion performance differed according to the combustion conditions. For the DTF, the burnout rate was correlated with the pore structure and microcrystalline structure, especially the latter. For isothermal combustion, the combustion characteristic parameter and microcrystalline structure d002 and Lc after high‐temperature treatment were strongly correlated. For nonisothermal combustion, the combustion characteristic parameters were strongly correlated with the volatile content. The above results can serve as a reference for evaluating the combustion performance of different fuels in a blast furnace using PCI.